Hydrodynamic investigation and characterization of a photo-bioreactor for microalgae cultivation - Mayol, Andres Philip (Animo Repository, 2017)
Bioreactors are promising growth container for microalgae species used in various disciplines such as chemical, pharmaceutical, biochemical, and environmental engineering. In addition, it has the advantage for closed environment conditions. One application of this is growing microorganisms that produces multifunctional products such as the microalgae. Microalgae are microorganism that has promise in biotechnology and energy sector. However, certain problem arises in cultivating microalgae in conventional bioreactors such as the bubble column bioreactor. Hence, ACCORDION bioreactor was generated to enhance mixing and mass transfer inside the bioreactor. This study, investigated the hydrodynamics of the conventional bioreactor (bubble column) and the ACCORDION bioreactor to see the difference of the two bioreactors in terms of gas hold up and mixing time. Computational Fluid Dynamics (CFD) was used as a tool to visualize gas-liquid fluid flow inside the bioreactor. Results show that there is a difference on gas hold up between the ACCORDION and the Bubble column bioreactor. As the flowrate increases, there is also an increase of gas hold up for both bioreactors. Mixing time results show that at lower flowrates there is a greater value on mixing time of the ACCORDION. However, when the flowrates reached the values of 0.4 VVM to 0.5 VVM the bubble column photo-bioreactor had greater mixing time. Hence, the geometry and gas flow rates gives influence mixing time on both photo-bioreactors. CFD simulation shows the visualization of both photobioreactors on air volume fraction and liquid circulation flow. Results indicated that in terms of liquid circulation on both photo-bioreactors, the ACCORDION had a better circulation than that of the bubble column. Fluid flow visualization show the different of gas and liquid flows of both reactors on different flow rates. To facilitate the growth of microalgae future studies can investigate the hydrodynamics of both reactors but using different fluid densities such as aqueous solutions which has thick density than water. Moreover, the addition of CO2 in the system will also show the effect of having CO2 in the bubble mixed with air. CFD simulation can be improved by adding Population balance method (PBM). In addition, having an advance meshing technique for the ACCORDION photo-bioreactor such as dynamic meshing can enhance the physics and model of the ACCORDION photo-bioreactor.